Measured data from sensor Dis at Attert for month 2006-02 - Hugo Hellebrand (4TU.Centre for Research Data, 2009)
measured water pressure
Parent item:
All data measured by discharge meter in Attert basin
Measuring instrument:
Useldange, Attert basin: Discharge meter
ISCO 4120 ultrasonic sensor (ceramic pressure membrane).
Measures water pressure (?).
The sensor is installed under a bridge (?).
Keywords: Physical Geography and Environmental Geoscience; Collection: Darelux - River Environment Luxemburg; climate; discharge; hydrology; river basin; Time: 2006-02